2017
DOI: 10.1007/s10994-017-5665-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and tracking topic-level influencers in the microblog streams

Abstract: Topic-level social influence analysis has been playing an important role in the online social networks like microblogs. Previous works usually use the cumulative number of links, such as the number of followers, to measure users' topic-level influence in a static network. However, they ignore the dynamics of influence and the methods they proposed can not be applied to social streams. To address the limitations of prior works, we firstly propose a novel topic-level influence over time (TIT) model integrating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The 50% cut-off reflected a previous online credibility study [20]. Follower count alone does not denote influencer status [33], and 'micro-influencers' with between 1000 and 100,000 followers are considered important as they tend to focus on a niche area [34,35]. To capture these topic-specific SMI, follower counts across Twitter, Facebook and Instagram were used, with the lower cut-off being 80,000 on one SM.…”
Section: Does the Influencer Always Make Clear Distinction Between Famentioning
confidence: 99%
“…The 50% cut-off reflected a previous online credibility study [20]. Follower count alone does not denote influencer status [33], and 'micro-influencers' with between 1000 and 100,000 followers are considered important as they tend to focus on a niche area [34,35]. To capture these topic-specific SMI, follower counts across Twitter, Facebook and Instagram were used, with the lower cut-off being 80,000 on one SM.…”
Section: Does the Influencer Always Make Clear Distinction Between Famentioning
confidence: 99%
“…While very few approaches have used manually handcrafted keywords to define multiple topics, [14,131], various other techniques, such as topic modeling [7,9,13,20,23,28,37,39,47,60,64,67,82,84,96,98,104,108,109,111,115,117,117,121,125,130,132], machine learning [85,108], and platform structures [50,126] are used to infer multiple topics in the literature. The way content is organized on a platform can be considered as a representation of a topic based on platform structures; e.g., a board on the Pinterest platform discusses a single topic.…”
Section: Topic Detectionmentioning
confidence: 99%
“…Therefore, it is essential to analyze the user influence at the topic level and determine the topic-based influential users. This can be considered as a granular study of influential user detection problem, and a vast amount of interest has been shown towards inferring topic-based influential users in the literature [13,26,37,38,64,69,78,98,111,125].…”
Section: Introductionmentioning
confidence: 99%
“…Each of the aforementioned studies has not considered the importance of hot event topic information content and user preferences. Literature in the context of event detection demonstrates that the influence of users in the social network is related to the relationship between users and topic while the influence of the same user is dissimilar under different topics [30]. Furthermore, these studies in [11], [23], [31], [32] focus on the effect of topic influence on user activation probability and ignored utilizing the popularity of topics, links between posts, and diffusion power of the users.…”
Section: Related Workmentioning
confidence: 99%